2009
DOI: 10.1093/eurheartj/ehp374
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary bone marrow cell transfer after myocardial infarction: 5-year follow-up from the randomized-controlled BOOST trial

Abstract: A single intracoronary application of BMCs does not promote a sustained improvement of LVEF in STEMI patients with relatively preserved systolic function. It is conceivable that a subgroup of patients with more transmural infarcts may derive a sustained benefit from BMC therapy. However, this needs to be tested prospectively in a randomized trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
150
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(161 citation statements)
references
References 21 publications
5
150
1
5
Order By: Relevance
“…3 -11 However, it remains controversial whether the short-term benefits of BMC transplantation could last for more than 12 months. The Bone Marrow Transfer to Enhance ST-Elevation Infarct Regeneration trial (BOOST) suggested that BMC therapy did not improve LVEF at 5-year follow-up, 12 while the Clinical Benefit and Long-Term Outcome After Intracoronary Autologous Bone Marrow Cell Transplantation in Patients With Acute Myocardial Infarction (BALANCE) study showed a long sustained benefit of BMC treatment. 13 In this systematic review referring randomized controlled trials with 12 months or longer follow-up data, we analyzed the chronic efficacy of intracoronary autologous BMC in patients with acute MI.…”
Section: Introductionmentioning
confidence: 99%
“…3 -11 However, it remains controversial whether the short-term benefits of BMC transplantation could last for more than 12 months. The Bone Marrow Transfer to Enhance ST-Elevation Infarct Regeneration trial (BOOST) suggested that BMC therapy did not improve LVEF at 5-year follow-up, 12 while the Clinical Benefit and Long-Term Outcome After Intracoronary Autologous Bone Marrow Cell Transplantation in Patients With Acute Myocardial Infarction (BALANCE) study showed a long sustained benefit of BMC treatment. 13 In this systematic review referring randomized controlled trials with 12 months or longer follow-up data, we analyzed the chronic efficacy of intracoronary autologous BMC in patients with acute MI.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, the influence of the timing of intracoronary BMDMNC delivery on LV function in patients with AMI undergoing primary PCI has infrequently been analyzed. Interestingly, a systemic review 40) has revealed that, compared with emergent transfusion (within 24 hour post-AMI) of BMDMNCs (ie, emergent transfer trials), [41][42][43] BMDMNC transfer at 4 to 7 days post-AMI 5,8,9) (ie, early trials) was superior to that within 24 hours in improving LV function and decreasing LV end-systolic dimensions. However, practically, because early cell delivery may not be possible for the majority of patients, the efficacy of autologous BM-DMNC delivery at either 3 days or 7 days or 2 to 3 weeks post-MI has been investigated by the TIME randomized trial 16) and the Late TIME randomized trial.…”
Section: Bmdmsc Transplantation Improved Heart Function -Role Of Immumentioning
confidence: 99%
“…44) The particularly noteworthy finding in the present study is that rapid implantation of BM-DMSC significantly improved the heart function after permanent AMI in the mini-pig model. Thus, we suggest that more clinical trials are needed to elucidate whether earlier BMDM-NC treatment compared with the timing reported in the current studies 5,8,9,16,[41][42][43][44] (ie, BMDMNC transfer at 4 to 7 days post-AMI) could provide an additional benefit of improving heart function and clinical outcome in patients after AMI. Our new findings with promising results (ie, very early treatment with BMDMNCs after onset of AMI) may, at least partially, support our suggestion.…”
Section: Bmdmsc Transplantation Improved Heart Function -Role Of Immumentioning
confidence: 99%
See 2 more Smart Citations